Proximate and Phytochemical Analysis of the Ethanol Extract of Abelmoschus manihot Leaves Collected from Tinoor Dua Village, North Tomohon, North Sulawesi - Gofarana Wilar; Jutti Levita; Lie Christian Giano Tikoalu; Indah Suasani Wahyuni (Faculty of Mathematic and Natural Science, Garut University, 2026)
The flowers of Abelmoschus manihot have been broadly studied in China for their phytochemical content and biological activities; however, the leaves have been explored only to a limited extent. In Manado, Sulawesi, Indonesia, the leaves of this plant are the most important ingredient in tinutuan porridge. The total phenols (TPC) and total flavonoids (TFC) in the leaves collected in Bogor, Manado, Tomohon, and Kotamobagu have been previously reported. This study aimed to provide data on the proximate and phytochemical composition (TPC, TFC, and quercetin levels) of the ethanol extract of A. manihot leaves collected from Tinoor Dua Village, North Tomohon, North Sulawesi, Indonesia. Extraction was carried out at room temperature using 70% ethanol. The phytochemical screening test was conducted according to a standard procedure for plant extracts. The proximate composition of the extract was analyzed in accordance with SNI 01-2891-1992. The TPC and TFC were determined by following the procedures outlined in SNI 01-2891-1992. Additionally, the TPC and TFC were also determined in accordance with SNI 01-2891-1992, and the procedures outlined in the Indonesian Herbal Pharmacopoeia were followed. Quercetin levels were analyzed using HPLC. Proximate analysis revealed 35.60% of total ash, 28.56% of carbohydrate, 18.31% of water, 11.01% of protein, and 6.53% of fat, whereas the TPC was 1350 mg GAE/100 g extract, the TFC was 2670 mg QE/100 g extract, and quercetin in the extract was 373.7 ± 0.18 mg/L. These findings will support further exploration for the development of A. manihot leaves as a nutritional food or nutraceutical supplement.